(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Privacy and confidentiality in medical care are deeply rooted in core professional ethical standards across a variety of health professions. Present project aimed to study perceptions of intern doctors regarding privacy and confidentiality in medical practice. Materials and methods: Total 100 intern doctors of GMERS Medical College, Valsad, Gujarat were subjected to pre-tested and pre-validated Likert scale type questionnaire regarding knowledge and awareness of privacy and confidentiality in medical practice after obtaining their informed written consent. Data obtained were analyzed via median score and tabulated. Results: Out of 100 respondents, 58 were male and 42 were female. Knowledge and awareness regarding many of the facts related to privacy and confidentiality of medical practice found to be satisfactorily with median score of more than 3. Professional secrecy is implied term of contract between doctor and patient, patient can sue the doctor for damages if disclosure is done without his consent and harm him and not in the interest of public, etc. showed median score of 3. Disclosure to parents without consent in case of major and breach of professional secrecy is professional misconduct of doctor showed median score less than 3. Conclusion: Intern doctors had little knowledge regarding disclosure to parents without consent in case of major and breach of professional secrecy is professional misconduct of doctor. Intern doctors were not sure about Professional secrecy is implied term of contract between doctor and patient and patient can sue the doctor for damages if disclosure is done without his consent and harm him and not in the interest of public. Knowledge and awareness regarding rest of the facts related to privacy and confidentiality of medical practice found to be satisfactorily among intern doctors.